Effectivity of Control Functional Inspectorat in Department National Education Sulawesi North Provincies. - Akerina, Gabriela; Posumah, Johhny; Tampongangoy, Deysi (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT   Education  is  one  of  Indonesia’s  development  strategy  are  directed  to  build  Indonesia.  Implementation of government policies in education programs require Monitoring, Evaluation and  Supervison. Therefore with the Implementation of a quality establishment of government officials,   then  appointed  Inspectorate,  as  Supervison  agency  development,  which  serves  to  oversee  the  performance  of  the  government  on  development  activities,  staffing  activities,  and  service  to  the  community.   The purpose of this study wanted to know how the Effectiveness of Functional Supervison  Inspectorate  on  National  Education  Departements  North  Sulawesi.  This  study  used  qualitative  methods.   Study   focused   (1)   the   supervision   process   on   the   Character   of   Effectiveness   is  Productivity,  Efficiency,  Satisfaction,  Flexibility,  and  Development.  (2)  Effec tive  monitoring  results, is the achievement of goal or program policies target that has been set. Source of data /   informants interviewed as many as 13 people consisting of 1 people Head office, 1 Treasurer, 1  holders program, and 10 person staff, and process data collection using interview techniques.    The  results  showed  that:  in  general,  that  functional  supervision  conducted  by  the  Inspectorate to the National Education Departments North Sulawesi, seen from the 5 character of  effectiveness  is  good.  The  timeliness  in  carrying  out  the  task,  achieve  its  intended  purpose.  In  accordance  with  purpose  of  supervision.  Their  competence  and  results  of  monitoring  that  is  capable of providing a change. Recommendations advice to the National Education Departements  of North Sulawesi, leaders more confirms duties and functions of each fields. In order to better,  structured, thorought and more appreciative of time in carrying out the task.    Keywords : Functional Supervison Inspectorate